Traditional Kelantanese portals: a study of form and content / Nurul Syazlina Che Yusof, Dr. Mumtaz Hj Mokhtar and Prof. Dr. Muliyadi Mahamood - Che Yusof, Nurul Syazlina; Mokhtar (Hj); Mahamood, Muliyadi (Prof. Dr. ) (Universiti Teknologi MARA, 2016)
Traditional Kelantanese portal is a form of Malay traditional door structure that can only be found at royal palaces and homes of dignitaries. In addition to its function as an entrance into the palace area, the portal is also a safety door for the palace. Since traditional portal belongs to the minorities, this heritage is rarely known by the public. The art of traditional Malay portals has never been researched and written thoroughly. The subject is briefly discussed in some books on art and architecture. Consequently, the purpose of this research is to study the history, form, visual elements, motifs, and meanings of the portals based on Erwin Panofsky's theories. This research will begin with the identification of the form and visual elements of traditional Kelantanese portals in the collection of the National Museum, Kuala Lumpur. In order to gain more information, interview sessions were conducted with the museum director, senior curator, cultural experts and academicians. The result of this study shows that in terms of history, traditional Kelantanese portals were influenced by the Patani Langkasuka style as Kelantan historically used to be under the rule of that government. Basically, traditional portal consists of four basic forms of architecture which are the pillars, wall, door and the head of the door. Meanwhile, there are four categories of motifs namely flora, fauna, cosmos, and calligraphy. Each of these motifs have different meaning and most of them are related to Malay philosophy and aesthetics, as well as cultural and religious belief. Finally, it can be concluded that traditional Malay portals should be conserved in terms of history, form and meanings for the future generation, as well as a form of respect and appreciation to the richness of Malay art and heritage.